Profesor Florian Śmieja doktorem honoris causa Uniwersytetu Wrocławskiego - Pasterska, Jolanta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The article presents report from the ceremony of awarding professor Florian Śmieja the highest academic dignity – the title of doctor honoris causa of the University of Wrocław for his contribution to the development of Polish science and literature and the Spanish studies.
Professor Florian Śmieja doctor honoris causa of the University of Wroclaw
Keywords: Florian Śmieja; Uniwersytet Wrocławski; doktor honoris causa; Wrocław; doctor honoris causa